Combined Piggyback Technique and Cavoportal Hemitransposition for Liver Transplant - Campsen, Jeffrey (Hindawi Publishing Corporation, 2010)
Portal Vein thrombosis (PVT) increases the difficulty of liver transplant; however, it is not an absolute contraindication. Cavoportal hemitransposition (CPH) is an option for patients with complete PVT and no alternative collateral vein. Our center often performs the piggyback technique for the hepatic vein reconstruction, which allows for great access to the recipient vena cava in patients with known complete PVT that may need a CPH preformed to successfully restore flow to the portal system of the donor liver. We describe the use of the piggy-back technique to prepare the vena cava for possible CPH in patients with known complete PVT.